Acquired hemophagocytic lymphohistiocytosis as initial manifestation of multiple myeloma: A case report and literature review - Mendes, Fernanda Rodrigues (Medicine (Baltimore), 2020)
INTRODUCTION: Hemophagocytic lymphohistiocytosis (HLH) is a condition characterized by a hyperinflammatory state and persistent macrophage activation, resulting in reactive phagocytosis of the hematopoietic elements. In children, it is usually a hereditary disorder, while in adults it is usually acquired secondary to viral infections, collagenoses, or tumors. Although accounting for 10% of hematologic malignancies, HLH is rarely associated with multiple myeloma (MM) and other plasmacytic dyscrasias. PATIENT CONCERNS: A 64-year-old Brazilian man seeked medical care with a 3-month history of intermittent fever, weight loss, night sweats, and progressive anemic symptoms. DIAGNOSIS: Total blood count showed severe bicytopenia (normocytic-normochromic anemia and thrombocytopenia), biochemical exams showed elevation of creatinine, as well as monoclonal peak in serum protein electrophoresis, high IgA dosage, and serum immunofixation with IgA kappa paraprotein. Bone marrow biopsy showed 30% of monoclonal and phenotypically anomalous plasmocytes, confirming the diagnosis of MM. Diagnosis of HLH was established by the presence of clinical and laboratory criteria: fever, splenomegaly, cytopenias, hypofibrinogenemia, hyperferritinemia, elevation of triglycerides, and several figures of erythrophagocytosis in bone marrow aspirate. INTERVENTIONS: The patient experienced pulse therapy with methylprednisolone for hemophagocytic lymphohistiocytosis, followed by initial therapy for multiple myeloma with cyclophosphamide and dexamethasone. OUTCOMES: Once the diagnosis of MM and secondary hemophagocytic syndrome was established, the patient had a rapid clinical deterioration despite the established therapeutic measures, evolving with cardiovascular failure, acute liver failure, acute disseminated intravascular coagulation, worsening renal dysfunction requiring dialysis support, respiratory dysfunction, and lowering of consciousness, characterizing rapid multiple organ dysfunction, ultimately leading to the death of the patient. INNOVATION: Here, we aimed to describe the sixth reported case of HLH associated with MM, according to cases cataloged in the PubMed database, and the first case evaluated by 18-fluordeoxyglucose positron emission tomography (18-FDG-PETCT). CONCLUSION: Our case report seeks to provide support for a better clinical and laboratory characterization of this rare paraneoplastic entity associated with MM, and aims to call the attention of hematologists and intensivists to this condition that falls within the scope of the differential diagnosis of rapid onset multiple organ failure in patients with plasmacytic neoplasms.